Study on small coal pillar in gob-side entry driving and control technology of the surrounding rock in a high-stress roadway - Wang, Wen; Wu, Yiheng; Lu, Xiaowei; Zhang, Guangjie (Frontiers in Earth Science, 2023)
The technology described as gob-side entry driving was adopted in the Zhaogu No. 1 mine to resolve the issues pertinent to mining succession tension, serious roadway deformation, and support difficulties. The key parameters of coal columns must be studied to ensure the stable support effect of along-air tunneling under high stress. A calculation for the vertical stress of a coal pillar is proposed, and the location of the breaking line in the top plate in the hollowed mining zone is determined by considering the breakage attributes of the basic uppermost large structure of the key layer, combined with the internal and external stress fields, and the limit equilibrium zone theories. FLAC3D software is employed to simulate the geological requirements of the mine, the characteristics of vertical stress of the coal pillar, and the surrounding rock of the roadway under the technical plan of leaving a 4.5-m coal pillar. The software is also used to verify and analyze the actual measurements. The outcomes suggest that the basic roof break is located at 2.65 m on the side of the coal pillar in the near mining area, and there is a trapezoidal internal stability region around the coal pillar that can provide lasting and stable support of the roadway. The displacement of the two helpers of the roadway is between 100 and 500 mm, and the displacements of the top and bottom plates are less than 300 mm, which ensures the roadway is surrounded by rock when the high-stress requirements occur. The safety of the roadway is determined under high-stress conditions.